Research on the Performance of a Liquid–Solid Triboelectric Nanogenerator Prototype Based on Multiphase Liquid - Wei Wang; Jin Yan; Xianzhang Wang; Hongchen Pang; Chengqi Sun; Yin Sun; Lijun Wang; Dapeng Zhang (Micromachines)
In recent years, liquid–solid triboelectric nanogenerators (L-S TENGs) have been rapidly developed in the field of liquid energy harvesting and self-powered sensing. This is due to a number of advantages inherent in the technology, including the low cost of fabricated materials, structural diversity, high charge-energy conversion efficiency, environmental friendliness, and a wide range of applications. As liquid phase dielectric materials typically used in L-S TENG, a variety of organic and inorganic single-phase liquids, including distilled water, acidic solutions, sodium chloride solutions, acetone, dimethyl sulfoxide, and acetonitrile, as well as paraffinic oils, have been used in experiments. However, it is noteworthy that the function of multiphase liquids as dielectric materials is still understudied. The “Multiphase Liquid Triboelectric Nanogenerator Prototype (ML-TENG Pro)” presented in this paper takes a single-electrode solid–liquid triboelectric nanogenerator as the basic model and uses lubricating oil and deionized water as dielectric materials. After verifying the stability of single-phase liquid materials (e.g., DI water, seawater, ethanol, etc.) for power generation, the power generation performances of oil–water two-phase, gas–oil–water three-phase (with a small number of bubbles), and gas–oil–water three-phase (with many bubbles) in open space are further investigated. COMSOL Multiphysics 6.0 software was used to investigate the material transport mechanism and formation of oil–water two-phase and gas–oil–water three-phase. Finally, this study presents the power generation performance of ML-TENG Pro in the extreme state of gas–oil–water three-phase “emulsification”. This paper outlines the limitations of the ML-TENG, named PRO, and suggests avenues for future improvement. The research presented in this paper provides a theoretical basis for evaluating the quality of lubricants for mechanical power equipment.